From chemotherapy to oncoviruses – modern methods of treatment in metastatic melanoma - Drobek, Hanna H.; Bergler-Czop, Beata S.; Miziołek, Bartosz (Dermatology Review/Przegląd Dermatologiczny, 2017)
Melanoma develops from neuroectodermal cells known as melanocytes. Recent studies have revealed an alarming increase in the annual incidence of this disease in Poland and worldwide. Although melanoma accounts for a small percentage of occurrences in comparison with all cancers, it develops rapidly, proceeding in a short time to the advanced stage of the disease; thus successful therapy of melanoma becomes the key solution. The early treatment dates back to dacarbazine, a cytostatic drug, giving a clinical response only in approximately 15% of patients. However, targeted molecular treatment and immunotherapy have been essential breakthroughs, including BRAF inhibitors and ipilimumab, announced recently as the discovery of the decade. Furthermore, later medical studies have led to surprising findings, a crucial example being oncolytic therapy which attenuated viruses. Talimogene (T-VEC) is the first drug of this kind approved in unresectable melanoma. Research on its therapeutic properties is still ongoing.